Proverbes et sentences dans La Celestina : traduction, effets de formes et effets de sens - Thomas Faye (Les Cahiers de Framespa)
In a semiotic approach focused on the study of literary translation, we consider the special case of the translation of the proverbs in La Celestina by Fernando de Rojas. The proverbs, in the discourse, are used to convince: the spanish procuress uses and abuses of proverbs, with the aim not only to seduce her interlocutors but also, with counter-examples, the reading public.The translator faces a dual challenge: restore the original diegetic persuasive charge, then allow the new reader to access the educational dimension.By studying the translation of proverbs to the French by Aline Schulman, we want to highlight the translation strategies implemented by the translator, but we also want to have some reflexion about the way the text is able to resist the translation, shows its own borders, bitween cohesion and dynamism of the meaning genesis.